(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
The present study was undertaken to prepare direct compressible tablets of nimesulide by altering its physical properties with the help of the method crystallo-co-agglomeration technology. Nimesulide is a widely used nonsteroidal anti- inflammatory drugs type of drug and is very useful in the treatment of arthritis. Because of its poor flowability character, tablets of nimesulide cannot be prepared by direct compression. An attempt has been taken to improve the tableting property by altering the micromeretic properties, like flow rate, Carr index, Hausner ratio and angle of repose. Conformation of improvement of compressibility and other processing problems was studied by Heckel analysis and Kawakita constant using a hydraulic press under a pressure of 0.5, 1, 2 and 4 tonnes for 10 s. The tablets were prepared by direct compression of nimesulide agglomerates using two different types of polymers, polyethelene glycol (PEG6000) and ethyl cellulose (EC) in different ratios (50, 100 and 200 mg).The drug release shows different patterns for the various percentages of PEG and EC.